Fever-Induced Brugada Syndrome. (21st March 2015) - Manohar, Sandhya; Dahal, Binaya Raman; Gitler, Bernard
Brugada syndrome is increasingly recognized as a cause of sudden cardiac death. Many of these patients do not get diagnosed due its dynamic and often hidden nature. We have come a long way in understanding the disease process, and its electrophysiology appears to be intimately linked with sodium channel mutations or disorders. The cardiac rhythm in these patients can deteriorate into fatal ventricular arrhythmias. This makes it important for the clinician to be aware of the conditions in which arrhythmogenicity of Brugada syndrome is revealed or even potentiated. We present such an instance where our patient's Brugada syndrome was unmasked by fever.